2013
DOI: 10.1111/1469-0691.12104
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of dengue virus 1 from autochthonous dengue fever cases in Croatia

Abstract: In the summer of 2010, two autochthonous dengue fever cases were detected in Croatia. Here we report the retrospective detection of an additional case of dengue fever, representing the first sustained autochthonous transmission in Europe since 1928. In addition, we present the phylogenetic analyses based on two sequences from the Pelješac peninsula, southern Croatia. The sequences were identified as dengue virus genotype 1 and recovered from two out of the three Pelješac patients in whom infection occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 8 publications
0
18
0
1
Order By: Relevance
“…In 2010, it became clear that even travelling to non-endemic regions, such as southern Europe, pose a risk to acquire dengue fever as illustrated by reports on autochthonous cases in France and Croatia. [3][4][5][6] It is noteworthy that this phenomenon is of concern for other arboviruses as well as demonstrated for chikungunya virus in Italy 12 and West Nile virus in Greece. 13 The epidemic in Madeira 7,8 illustrates the recent reemergence of DENV in Europe.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2010, it became clear that even travelling to non-endemic regions, such as southern Europe, pose a risk to acquire dengue fever as illustrated by reports on autochthonous cases in France and Croatia. [3][4][5][6] It is noteworthy that this phenomenon is of concern for other arboviruses as well as demonstrated for chikungunya virus in Italy 12 and West Nile virus in Greece. 13 The epidemic in Madeira 7,8 illustrates the recent reemergence of DENV in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In Madeira, only DENV-1 was circulating during the epidemic. Sequencing of the E/NS1 junction genome fragment is useful for accurate determination of the causing genotype as shown in cases in Croatia 6 and imported to Europe 11 and can contribute to the epidemiology of the disease. The phylogenetic analysis of this study was also based on this fragment and revealed that isolate BE56 of the Belgian traveler falls within the South American lineage of the American/African (V) genotype of DENV-1, being most closely related to the isolate detected in Colombia in 2008.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…However, they could have been occurred since some cases may goes under detected as happened in Croatia for DENV infection (Kurolt et al, 2013). There is a clear overlap of the peaks of imported cases and the vector's activity (Figure 6).…”
Section: Discussionmentioning
confidence: 99%